2022
DOI: 10.3390/app122110733
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Rollover Angle of a Self-Propelled Radish Harvester for Different Load Conditions

Abstract: This study was focused on the stability analysis of the self-propelled radish harvester. A 3D simulation model was developed using RecurDyn and used to analyze the rollover angle. The rollover angle of the original radish harvester was analyzed and checked to see if it satisfied the standard overturning angle (i.e., 30°). To improve it, three simulated weights (50, 100, and 150 kg) were added to three positions (front, center, and rear). The rollover angle of the radish harvester was slightly less than the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…According to the agricultural machine test standards, the overturning angle should be at least 30 • [48]. However, Kim et al [43] found that the minimum longitudinal overturning was 29.19 • ~33.25 • . Furthermore, according to ISO 16251-2 [53], the allowable range of the overturning angle depending on the off-road agricultural machine is 15 • ~45 • .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the agricultural machine test standards, the overturning angle should be at least 30 • [48]. However, Kim et al [43] found that the minimum longitudinal overturning was 29.19 • ~33.25 • . Furthermore, according to ISO 16251-2 [53], the allowable range of the overturning angle depending on the off-road agricultural machine is 15 • ~45 • .…”
Section: Discussionmentioning
confidence: 99%
“…The tractor used does not have suspension for ease of calculating the change in CoG. This assumption may affect the tractor balance but was not considered in this rollover angle test [43]. It is assumed that the center of gravity G (a, c, h) of the tractor is located on the line of AM.…”
Section: Mathematical Model Of the Tractor Rollovermentioning
confidence: 99%
See 1 more Smart Citation
“… Self-propelled radish harvester ( a ), three-dimensional model of a tractor-mounted radish collector, and ( b ) impact plate installation position (A,A), load-out conveyor (B,B), and pull-out conveyor (C,B). Adapted from [ 18 , 20 ]. …”
Section: Figurementioning
confidence: 99%
“…Hence, there is a limitation in knowing the rollover angle in all directions. Kim et al [33] used simulations to measure the rollover angle of a tractor more accurately in all directions instead of just one direction, which allowed them to analyze the rollover angle at different angles and situations, helping them to develop a method to prevent rollover accidents. By leveraging these simulations, it will be possible to rotate the tractor and derive the rollover angle from all sides.…”
Section: Introductionmentioning
confidence: 99%